COMPARATIVE ANALYSIS OF NUMBER CATEGORY IN ENGLISH AND UZBEK LANGUAGES - Norboyeva Mohinur, Mukhamadiyev Aziz Shavkatovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article provides a comparative analysis of the number category in English and Uzbek, examining the ways in which singular, dual, and plural forms are used in each language to express quantity. English has a more straightforward number system with numerical markers, whereas Uzbek has a more complex number system with dual forms and distinct suffixes for various values. Whereas English's usage of numerical markers reflects its grammatical structure, Uzbek's dual forms lend the language subtlety. By looking at these variations, we can learn more about how languages influence communication styles and serve as mirrors for cultural values.